Two Poems - Kalyanasundaram, Srisrividhiya (The Trumpeter)

(untitled) (Athabasca University Press, 2022)
How do we open our sense of being? What is to be our intrinsic nature - iyalbu from which action flows freely bound by the laws of a chosen, crafted consciousness? What is this residual loneliness of being that makes us who we are as part of the greater earth? How do we create a sense of belonging? How do we find ourselves - trillions of years old in star dust and tracing our ways back to a single ancestor of life?